Patient satisfaction with the service at Menopause Clinic, Maharaj Nakorn Chiang Mai hospital - Somsak Chaovisitsaree (2018)
Objective: To evaluate patient satisfaction of service at the Menopause Clinic and to identify factors affecting patient satisfaction. Material and Method: Cross sectional descriptive study was conducted at the Menopause Clinic, Maharaj Nakorn Chiang Mai hospital. Three hundred twenty six subjects were included. The questionnaire consists of two parts, demographic and patient satisfaction. The patient satisfaction was evaluated in five aspects. Results: The overall patient satisfaction level was good (mean 4.2 ± 0.71). The satisfactions about service behavior, quality of care and health information were in excellent level (mean 4.29 ± 0.69, 4.25 ± 0.65, and 4.26 ± 0.69, respectively). The satisfaction about clinic facilities/conveniences and medical expense were in good level (mean 3.83 ± 0.79 and 3.87 ± 0.75). There are three variables that could affect patient satisfaction: Occupation and level of education affected satisfaction in medical expense aspect (p < 0.001 and p < 0.05) and number of visits affected the clinic facilities/convenience aspect (p < 0.05). Conclusion: Some patient characteristics affected the patient satisfaction. However, system and structure of service in different setting hospitals are of concerned.